Final answer:
To find (f+g)(x), add the functions f(x) and g(x) together. To find (f+g)(-2), substitute -2 for x in the expression.
Step-by-step explanation:
To find (f+g)(x), we need to add the functions f(x) and g(x) together. To do this, we add the corresponding terms of the two functions:
(f+g)(x) = f(x) + g(x) = (-10x^2 + 9x + 2) + (-9x^2 - 10)
Combining like terms, we get:
(f+g)(x) = -19x^2 + 9x - 8
To find (f+g)(-2), we substitute -2 for x in the expression we obtained for (f+g)(x):
(f+g)(-2) = -19(-2)^2 + 9(-2) - 8
Simplifying further:
(f+g)(-2) = -19(4) - 18 - 8
(f+g)(-2) = -76 - 18 - 8
(f+g)(-2) = -102